Досвід збереження вікових дерев та історичних насаджень у дендрологічному парку “Олександрія” НАН України - Galkin, S.I.; Dragan, N.V.; Doiko, N.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
The richness of centenary trees in arboretum Olexandria of the NAS of Ukraine, their role in park landscapes is shown. The event on the individual care and treatment of these trees is elucidated. The experience of rehabilitation of historic landscape compositions of the park Olexandria is analysed. The measures on protection and increasing of old trees vitality is outlined.